Sistem Informasi Borongan ( Siborong ) Untuk Menghitung Estimasi Biaya Dalam Pembangunan Rumah Berbasis Web - Agusti, Yoga; Samsudin; Triase (Jurnal Mahajana Informasi, 2024)
Building construction is a technique or method of erecting a building object according to what will be built. Establishing a building requires planning the calculation of the estimated costs incurred. The calculation of the estimated cost must be calculated carefully with the cost of making it such as the materials needed and the labor costs incurred. Prospective home owners do not have a reference for the estimated capital budget until a building is completed. Calculation of the construction of a house really needs maturity in planning, because it is not far from the costs incurred, so there is no loss of material prices and use of materials at the time of construction. Seeing this situation, prospective homeowners need to know the estimated costs incurred in building a house by conducting an analysis to build an information system to calculate web-based cost estimates to make it easier for prospective homeowners to know the estimated costs incurred until the house is completed. This information system provides filling specifications for the size of a one-story house, specifications for the number of rooms and also consists of two choices of material classes used. This information system is built using framework laravel, with programming language PHP, development method Rapid Application Development (RAD), and MySQL as the system database.